Decreased Incidence of Hepatocellular Carcinoma in Hepatitis B Vaccinees: A 20-Year Follow-up Study - Chang, Mei-Hwei; You, San-Lin; Chen, Chien-Jen; Liu, Chun-Jen; Lee, Chuan-Mo; Lin, Shi-Ming; Chu, Heng-Cheng; Wu, Tzee-Chung; Yang, Sheng-Shun; Kuo, Hsu-Sung; Chen, Ding-Shinn (JNCI : Journal of the National Cancer Institute, 2009)
Background Hepatitis B virus (HBV) infection is a major cause of hepatocellular carcinoma. This population-based study aimed to investigate whether prevention of hepatocellular carcinoma by the universal Taiwanese HBV vaccine program, launched in July 1984, has extended beyond childhood and to identify the predictors of hepatocellular carcinoma for vaccinated birth cohorts. Methods Data on 1958 patients with hepatocellular carcinoma who were aged 6–29 years at diagnosis in Taiwan between 1983 and 2004 were collected from two national hepatocellular carcinoma registries. Age- and sex-specific incidence among vaccinated and unvaccinated birth cohorts were analyzed by using Poisson regression models. All statistical tests were two-sided. Records of 64 hepatocellular carcinoma patients and 5 524 435 HBV vaccinees who were born after the initiation of the vaccination program were compared for HBV immunization characteristics during infancy and prenatal maternal hepatitis B surface antigen (HBsAg) and e antigen (HBeAg) serostatus. Results Hepatocellular carcinoma incidence was statistically significantly lower among children aged 6–19 years in vaccinated compared with unvaccinated birth cohorts (64 hepatocellular cancers among vaccinees in 37 709 304 person-years vs 444 cancers in unvaccinated subjects in 78 496 406 person-years, showing an age- and sex-adjusted relative risk of 0.31, P < .001, for persons vaccinated at birth). The risk of developing hepatocellular carcinoma for vaccinated cohorts was statistically significantly associated with incomplete HBV vaccination (for those who received fewer than three doses of HBV vaccine, odds ratio [OR] = 4.32, 95% confidence interval [CI] = 2.34 to 7.91); with prenatal maternal HBsAg seropositivity (OR = 29.50, 95% CI = 13.98 to 62.60); with prenatal maternal HBeAg seropositivity (with administration of hepatitis B immunoglobulin at birth, OR = 5.13, 95% CI = 2.24 to 11.71; and without it, OR = 9.43, 95% CI = 3.54 to 25.11). Conclusion The prevention of hepatocellular carcinoma by this HBV vaccine extends from childhood to early adulthood. Failure to prevent hepatocellular carcinoma results mostly from unsuccessful control of HBV infection by highly infectious mothers.